Common Challenges Faced By Rural Principals: A Review of the Literature - Jane P. Preston; Brittany A. E. Jakubiec; Robin Kooymans (The Rural Educator, 2013)
Within this article, we thematically present common challenges associated with the role of the rural principal. In this literature review, we delimit our search to work published from 2003–2013. A limitation of this study is that it represents data predominantly from American, Canadian, and Australian rural settings, restricting a global applicability of results. Findings highlight that many rural principal candidates face a hiring disadvantage if they do not have a historical connection with the community advertising a position. Additional challenges include juggling diverse responsibilities, lack of professional development and resources, gender discrimination, and issues surrounding school accountability and change. This information is beneficial for researchers, policymaker, senior educational leaders, principals, vice-principals, teachers, parents, and community members interested in school leadership within rural communities. We conclude that to be successful, rural principals must be able to nimbly mediate relations within the local community and the larger school system.